Ex Ante Moral Hazard Pada Sistem Jaminan Kesehatan Nasional (JKN) di Indonesia - Putra, Fajar Nurhaditia (Jurnal Ekonomi Kesehatan Indonesia, 2020)
This paper contributes to the empirical evidence of ex ante moral hazard on the National Health Insurance System (NHIS) in Indonesia. We find that JKN participation has a negative relationship with physical activity and positive relationship with smoking spending. Furthermore, by calculating marginal effect we obtained that JKN participation reduce the probability of physical activity by 2.7% and also reduce the intensity of individual physical activity. For the smoker, JKN Participation is expected increase in their spending for smoking. The result indicates that there is an evidence of ex ante moral hazard since there is a positive relationship between JKN participation and risky health behaviors such as physical activity and smoking behavior.